2012
DOI: 10.1097/htr.0b013e3182236299
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Driving Capacity After Traumatic Brain Injury

Abstract: There is no sound basis at present for predicting driving capacity after traumatic brain injury because most studies have methodological limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 83 publications
(22 reference statements)
0
34
0
Order By: Relevance
“…Parameters such as length of coma duration and performance on neuropsychological assessments, particularly the Trail Making B test, have been shown to predict return to driving after TBI [29]. This study also found a trend towards higher education in the TBI drivers compared to the TBI non-drivers.…”
Section: Discussionmentioning
confidence: 70%
“…Parameters such as length of coma duration and performance on neuropsychological assessments, particularly the Trail Making B test, have been shown to predict return to driving after TBI [29]. This study also found a trend towards higher education in the TBI drivers compared to the TBI non-drivers.…”
Section: Discussionmentioning
confidence: 70%
“…The influence of cognitive deficits on driving fitness has been extensively studied, especially in older drivers and those with dementia of Alzheimer type, stroke and/or traumatic brain injury (TBI) [2]. Previous literature states that $40-80% of TBI and stroke survivors resume driving [3][4][5][6][7][8]. However, many patient groups that participate in international studies do not receive formal medical and/or psychological evaluations due to differences in national legislations and other reasons [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the condition and severity of injury may predict driving outcomes, and therefore affect family members' experiences specific to driving disruption (D'apolito et al, 2013). Predictors of return to driving are complex, and can be influenced by many other factors such as levels of community integration, duration of stay in hospital, pain levels, physical and cognitive processes, and behavioural issues Ortoleva et al, 2012). Furthermore, external factors such as the availability of resources in healthcare contexts, waiting lists, and the practical and symbolic meaning of driving may affect the individual and family members' experience of driving disruption Liddle, Fleming, et al, 2012).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In addition, driving disruption following an ABI is often perceived as a temporary rather than permanent cessation. There is a substantial focus on returning to driving in the ABI literature and the majority of research has examined the processes, predictors and assessment of safe return to driving (Aslaksen, Orbo, Elvestad, Schafer, & Anke, 2013;Bottari, Lamothe, Gosselin, Gelinas, & Ptito, 2012;Ortoleva, Brugger, Van der Linden, & Walder, 2012). In one study of individuals with traumatic brain injury (TBI), 48% of non-drivers expressed a strong desire to return to driving (Rapport, Bryer, & Hanks, 2008).…”
Section: Background and Significance Of Thesis "There Are Just Four Kmentioning
confidence: 99%
See 1 more Smart Citation